Microalgae biomass as a sustainable source for biofuel, biochemical and biobased value-added products: An integrated biorefinery concept. (1st January 2022) - Siddiki, Sk. Yasir Arafat; Mofijur, M.; Kumar, P. Senthil; Ahmed, Shams Forruque; Inayat, Abrar; Kusumo, F.; Badruddin, Irfan Anjum; Khan, T.M. Yunus; Nghiem, L.D.; Ong, Hwai Chyuan; Mahlia, T.M.I.
Graphical abstract: Highlights: Biorefinery concept for sustainable processing of microalgae biomass has been discussed. Reactor technologies for cultivating microalgae has been reviewed. Factors affecting the microalgae culture system has been reviewed. Different technologies to convert microalgae into biofuel and value-added products have been presented. The utilisation of a biorefinery concept can make the valorisation of microalgae economically viable. Abstract: Microalgal biomass has been proved to be a sustainable source for biofuels including bio-oil, biodiesel, bioethanol, biomethane, etc. One of the collateral benefits of integrating the use of microalgal technologies in the industry is microalgae's ability to capture carbon dioxide during the application and biomass production process and consequently reducing carbon dioxide emissions. Although microalgae are a feasible source of biofuel, industrial microalgae applications face energy and cost challenges. To overcome these challenges, researchers have been interested in applying the bio-refinery approach to extract the important components encapsulated in microalgae. This review discusses the key steps of microalgae-based biorefinery including cultivation and harvesting, cell disruption, biofuel and value-added compound extraction along with the detailed technologies associated with each step of biorefinery. This review found that suitable microalgae species are selected based on their carbohydrate, lipid and protein contents and selecting the suitable species are crucial for high-quality biofuel and value-added products production. Microalgae species contain carbohydrates, proteins and lipids in the range of 8% to 69.7%, 5% to 74% and 7% to 65% respectively which proved their ability to be used as a source of value-added commodities in multiple industries including agriculture, animal husbandry, medicine, culinary, and cosmetics. This review suggests that lipid and value-added products from microalgae can be made more economically viable by integrating upstream and downstream processes. Therefore, a systematically integrated genome sequencing and process-scale engineering approach for improving the extraction of lipids and co-products is critical in the development of future microalgal biorefineries.